A Dynamic System Model: Flat Export Duty of Cocoa Beans (Hs 180100) For Downstreaming of Indonesian Cocoa Industry and Farmers - Gobel, Muhammad Rizq (YUME : Journal of Management, 2025)
Indonesia's progressive export duty of 0–15% on cocoa beans aims to protect raw materials, enhance value-added processing, and strengthen domestic industry competitiveness. While this policy has boosted exports of cocoa derivative products, it has also negatively impacted cocoa bean production and domestic prices. This study employs needs analysis, Day Competitiveness Analysis, and a conceptual model incorporating causal loop and stock-and-flow diagrams. Model validation uses structural and performance validity tests, including Root Mean Square Percentage Error (RMSPE), Absolute Mean Error (AME), and Absolute Variance Error (AVE). Key variables analyzed include cocoa bean production and processed cocoa output.Revealed Comparative Advantage (RCA) values from 2010 to 2023 indicate a decline in Indonesia’s cocoa competitiveness. The study projects that a flat export duty policy would positively influence farmer income, cocoa bean exports, production levels, competitiveness, and national cocoa stocks. Higher farmer income is expected to strengthen the agro-industrial system and ensure long-term sustainability. To enhance domestic cocoa bean absorption, increasing the involvement of micro, small, and medium enterprises (MSMEs) in processing activities is essential. This strategy will reduce reliance on imports, boost cocoa derivative exports, and create a more resilient and competitive cocoa industry aligned with national and global market demands.